How can merchant responses repair potential consumers’ trust after negative online product reviews? An attibution theory perspective - Wang, Yang; Zhang, Gangren; Chai , Gaixian; Yang, Bo (Transformations In Business & Economics, 2025)
For online merchants, providing clear and appropriate feedback explanations to address negative product reviews is crucial for mitigating consumer trust crises triggered by service failures and ensuring the sustainable growth of e-commerce. However, existing studies on merchant responses predominantly rely on traditional service recovery theories. In actual e-commerce platforms, while conventional remedial measures such as apologies and compensation help potential consumers achieve psychological balance and perceive fairness, they place greater emphasis on merchants’ attributional explanations for transaction failures. To explore how merchants’ feedback attributions influence trust damage and recovery following negative product reviews, drawing on attribution theory, an attribution model for restoring potential consumer trust was constructed, and using scenario-based experiments involving 467 typical young online shoppers, the impact of responsibility locus, controllability, and stability of merchants’ feedback on the trust damage and recovery of potential consumer. Results indicate that: (1) External attributions in causal explanations for negative reviews result in significantly less trust damage compared to internal attributions. (2) For attribute-level explanations, uncontrollable attributions are more effective than controllable attributions in reducing trust damage. (3) Unstable attributions outperform stable attributions in mitigating trust erosion. This study offers a novel perspective on service recovery through merchant feedback, thereby expanding the application scope of attribution theory. The conclusions obtained from this study offer actionable recommendations for operators to strategically employ attributional explanations to counterbalance the adverse effects of negative reviews.